Effect of Garlic (Allium sativum) Infusion On The Time of Death of Ascaridia galli - Ida Yuniarti; Suzanita Utama; Setiawan Koesdarto; Lucia Tri Suwanti; Ngakan Made Rai Widjaja (Universitas Airlangga, 2017)
Infectious disease is a major problem for animal husbandry. One of infectious disease is caused by Ascaridia galli (A. galli). Ascaridiasis occurs in either broiler or layer that caused decrease of meat and egg productions. Garlic (Allium sativum) contain alicinÂ that have the ability to kill parasites.This research was conducted to determine the effect of garlic on time of death of A. galli. In this research used A. galli with length 7-11 cm regardless the sex. The treatment used local (Indonesian garlic), kating and single garlic with concentration of 39.50%, 62.40% and 98.60%. The negative control used NaCl physiology (0.9 %). The result showed that all the treatment group can shortened the time of death of A. galli compared to control. The time of death of A. galli on local garlic infusion with 39.50 % concentration was 6.24 hours, on 62.40 % concentration was 4.94 hours and on 98.60 % concentration was 3.97 hours, kating garlic infusion on 39.50 % concentration was 5.08 hours on 62.40 % concentration was 3.81 hours, on 98.60 % concentration was 2.96 hours, single garlic infusion on 39.50 % concentration was 5.4 hours, on 62.40 % concentrationÂ was 3.86 hours, on 98.60 % concentration was 3.83 hours. The best treatment was kating garlic on 98.60% concentration because give shortest time of death.